Pengaruh Pelatihan dengan Menggunakan Modul Terhadap Peningkatan Pengetahuan dan Sikap Operator dan Pemilik Depot Air Minum di Kota Bandung - oci - sarkosi (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Knowledge is a very important factor to shape a person's behavior. Behavior based on knowledge will last longer than behavior that is not based on knowledge. The purpose of this study was to analyze the differences in knowledge and attitudes of operators and owners of Drinking Water Depots (DAM) before and after training using the module. The research method used is the one group pretest and posttest design model. The module trial subjects numbered 35 people, namely 23 DAM owners and 12 DAM operators in Bandung City. Sampling is done by pursuive sampling technique. Differences in the level of knowledge and attitudes of DAM operators and owners before and after DAM sanitation hygiene training were tested using the Wilcoxon Signed Rank Test. The results showed that there were significant differences between the level of knowledge before and after training (p = 0.001) and there was no significant difference between attitudes before and after training on DAM sanitation hygiene using the module (p = 0.534). The conclusion of this study is that DAM sanitation hygiene training using modules can improve the training participants' knowledge but does not change the attitudes of trainees.